Device Engineered Organic Transistors for Flexible Sensing Applications. Issue 22 (2nd February 2016) - Zang, Yaping; Huang, Dazhen; Di, Chong‐an; Zhu, Daoben
Abstract : Organic thin‐film transistors (OFETs) represent a promising candidate for next‐generation sensing applications because of the intrinsic advantages of organic semiconductors. The development of flexible sensing devices has received particular interest in the past few years. The recent efforts of developing OFETs for sensitive and specific flexible sensors are summarized from the standpoint of device engineering. The tuning of signal transduction and signal amplification are highlighted based on an overview of active‐layer thickness modulation, functional receptor implantation and device geometry optimization. Abstract : Recent efforts in developing highly sensitive and specific flexible sensors in terms of active‐layer thickness modulation, functional receptor implantation, and device geometry optimization are briefly summarized with an outlook on future requirements.